Day 4 Thu, November 13, 2014 2014
DOI: 10.2118/172024-ms
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Flood Produced Water Treatment Trials

Abstract: Polymer enhanced oil recovery (EOR) operation has been implemented for the production of oil from difficult mature oilfields in Oman. The polymer used in this EOR technique to sweep oil toward production wells is resulting in the generation of polymer flood produced water (PFPW) of increasing viscosity. Current methods of treating oilfield produced water must be reconsidered for the effective treatment of such PFPW of changing quality. In a previous study, the utilization of polyaluminum chlorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…• Water treatment costs required to meet water quality standards for polymer preparation, water re-injection and/or water disposal (Al-Kalbani et al, 2014c;Al-Maamari et al, 2014;Batonyi et al, 2016;Henthorne, Walsh & Llano, 2013;Jacob et al, 2015;Rambeau et al, 2014Rambeau et al, & 2015Wu et al, 2013;Yang, L., Zhihua, W., Xianglong, Z., & Shanzhe, W., 2015).…”
Section: Summary Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Water treatment costs required to meet water quality standards for polymer preparation, water re-injection and/or water disposal (Al-Kalbani et al, 2014c;Al-Maamari et al, 2014;Batonyi et al, 2016;Henthorne, Walsh & Llano, 2013;Jacob et al, 2015;Rambeau et al, 2014Rambeau et al, & 2015Wu et al, 2013;Yang, L., Zhihua, W., Xianglong, Z., & Shanzhe, W., 2015).…”
Section: Summary Discussionmentioning
confidence: 99%
“…However, most of the studies documented in the literature mainly focus its attention on emulsion stability and its impact on oil-water separation, water treatment and production facilities (i.e. nutshell filters, heater treaters) due to the back produced polymer (Al-Kalbani et al, 2014;Al-Maamari et al, 2014;Bartz and Gotterba, 2015;Delamaide et al, 2014b;Geremia, and Bennetzen, 2016;Jacob et al, 2015;Rambeau, O., Jacob, M., Jouenne, S., & Cordelier, P., 2014;Wu et al, 2013;Wylde, Slayer & Barbu, 2013;Yang, Zhihua, Xianglong & Shanzhe, 2015;Zheng, F., Quiroga, P., & Sams, G. W., 2011).…”
Section: Water Emulsions In the Presence Of Polymersmentioning
confidence: 99%
“…It has been reported that the viscosity of the back produced water can reach few centipoises. Conventional water treatment technologies are directly impacted by the increase of viscosity (Al Kalbani 2014;Al-Maamari 2014;Zheng 2011). Loss of efficiency can reach more than 50% for flotation devices, and up to 90% for hydrocyclones.…”
Section: Water Treatmentmentioning
confidence: 99%
“…Combining chemicals is a promising way to get good water quality. Use of complex coagulants optimizing the flotation has been reported (Al Maamari 2014;Deng 2011;Zhang 2015). However, avoiding the formation of deposits, depending on their type, is a paramer to consider as well, as it has a great impact on process maintenance.…”
Section: Bench Lab Tests On Synthetic and Real Viscosified Produced Wmentioning
confidence: 99%